Lonely adolescents exhibit heightened sensitivity for facial cues of emotion. Issue 2 (17th February 2017) - Vanhalst, Janne; Gibb, Brandon E.; Prinstein, Mitchell J.
ABSTRACT: Contradicting evidence exists regarding the link between loneliness and sensitivity to facial cues of emotion, as loneliness has been related to better but also to worse performance on facial emotion recognition tasks. This study aims to contribute to this debate and extends previous work by (a) focusing on both accuracy and sensitivity to detecting positive and negative expressions, (b) controlling for depressive symptoms and social anxiety, and (c) using an advanced emotion recognition task with videos of neutral adolescent faces gradually morphing into full-intensity expressions. Participants were 170 adolescents (49% boys; M age  = 13.65 years) from rural, low-income schools. Results showed that loneliness was associated with increased sensitivity to happy, sad, and fear faces. When controlling for depressive symptoms and social anxiety, loneliness remained significantly associated with sensitivity to sad and fear faces. Together, these results suggest that lonely adolescents are vigilant to negative facial cues of emotion.